Generation of an induced pluripotent stem cell (iPSC) line (IGIBi026-A) derived from Wilson disease patient harboring compound heterozygous mutations [c.2165dupT (p.R723Efs31) and c.C813A (p.C271*)] in the ATP7B gene - Bhaskar Jyoti Saikia; Juhi Bhardwaj; Arti Saini; Roopa Rajan; Binukumar B.K (Stem Cell Research)
Wilson disease (WD) is a rare autosomal recessive disease caused due to mutations in the ATP7B gene. Here, we describe the establishment of an induced pluripotent stem cell (iPSC) line derived from peripheral blood mononuclear cells (PBMCs) of a WD patient with compound heterozygous mutations in the ATP7B gene [c.2165dup (p.R723Efs31) and c.C813A (p.C271*)] by using integration-free Sendai virus reprogramming system.